Correlation Between the Degree of Midline Shift in Computed Tomography Scan of Brain and Level of Consciousness of the Patients with Acute Spontaneous Intracerebral Haemorrhage (Sir Salimullah Medical College Journal, 2023)
Background: Intracerebral hemorrhage (ICH) is the second most common cause of stroke, following ischemic stroke, but accounts for a disproportionate amount of cerebrovascular mortality and morbidity. The extent of midline shift, observed on computed tomography (CT) scans, has been recognized as an important radiological finding associated with the severity of ICH.Objective: To evaluate correlation between the degree of midline shift in computed tomography scan of brain and level of consciousness of the patients with acute spontaneous intracerebral haemorrhage.Material and method: This cross-sectional study was carried out in 100 patients, out of this 50 had spontaneous intracerebral hemorrhage with mass effect and 50 had spontaneous intracerebral hemorrhage without mass effect taken as the control group, the age range from 30-75 years. These patients were purposively collected from the Department of Radiology and Imaging in collaboration with Department of Medicine, Neuromedicine and Neurosurgery of Dhaka Medical College Hospital, Dhaka. All the patients were evaluated by CT findings. On admission Glasgow Coma Scale (GCS) score were recorded from participant’s treatment sheet and reviewed by the senior Neurologist after taking permission of the authority.Results: This study shows there is significant inversely correlation of the GSC score with degree of midline shift measure using septum pellucidum shift (P